Management by obejectives at Eulogio Amang Rodriquez Institute of Science and Technology a case study - Guimary, Benjamin U. 1925-
This study identified the projects and activities of the Institute in relation to four expected outcomes--career development, professional skills improvement, participation in the development programs of the New Society, and qualitative aspects of personal development. It involved all 292 provisional and permanent personnel. MBO was successfully implemented in 1976-1977, with significant relationship between the supervisor's rating and the employee's self-rating. Some significant benefits realized included understanding of institutional goals, planning, self-direction in achieving goals, improved participation, motivation, performance appraisal and decision making but the process was time-consuming, difficult, and met some resistance.